Analisis Kesantunan Berbahasa Siswa Kepada Guru dan Siswa terhadap Siswa dalam Proses Pembelajaran di SMAN 1 Takalar - Nur Hikmah; Nurfathana Mazhud; Andi Puspitasari (Journal on Education, 2024)
This research aims to analyze the language politeness of students towards teachers and students towards students in the learning process. This analysis is shown from the form of polite language used and applying the principles of polite language. Qualitative descriptive research methods were used to answer this research. Techniques for collecting data include note-taking, observation, interviews and documentation. The research population is the language events of students and students to teachers and students to students in the Indonesian language teaching and learning process. Data analysis in this research uses qualitative descriptive analysis methods. The results of the research show that the forms of language politeness in student-to-teacher and student-to-student interactions are (1) declarative sentences complying with the maxims of wisdom, respect and consensus; (2) interrogative sentences obey the maxim of wisdom, and are appreciated; (3) imperative sentences obey the maxims of wisdom; (4) exclamative sentences obey the maxims of wisdom.